2007
DOI: 10.4049/jimmunol.178.3.1573
|View full text |Cite
|
Sign up to set email alerts
|

Necrotic Tumor Cell Death In Vivo Impairs Tumor-Specific Immune Responses

Abstract: The manner in which cells die is believed to have a major impact on the nature of immune responses to their released Ags. In this study, we present the first direct analysis of tumor-specific immune responses to in vivo occurring tumor cell death through apoptosis or necrosis. Mice bearing thymidine kinase-transfected tumors were treated either with ganciclovir to induce tumor cell apoptosis in vivo or a vascular targeting agent, ZD6126, to induce tumor cell necrosis in vivo. In contrast to tumor apoptosis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…90 HMGB1 release has been considered as a potential way of inducing an immune response against dying tumor cells undergoing necrosis. However, several studies showed that necrotic cells were unable to trigger an immune response 91,92 when injected in vivo, in contrast to the initial expectations. Recently, it has been found that tumor cells that undergo apoptosis in vitro, in response to anthracyclines, could mediate a potent antitumor vaccination effect when they were injected subcutaneously into syngeneic immunogenic mice.…”
mentioning
confidence: 40%
“…90 HMGB1 release has been considered as a potential way of inducing an immune response against dying tumor cells undergoing necrosis. However, several studies showed that necrotic cells were unable to trigger an immune response 91,92 when injected in vivo, in contrast to the initial expectations. Recently, it has been found that tumor cells that undergo apoptosis in vitro, in response to anthracyclines, could mediate a potent antitumor vaccination effect when they were injected subcutaneously into syngeneic immunogenic mice.…”
mentioning
confidence: 40%
“…In addition, Ullman et al (18) reported that autophagy activates necrosis in apoptosis-deficient mouse embryonic fibroblasts. Gamrekelashvili et al (19) reported that necrosis may inhibit cancer recurrence by acquiring tolerance without inducing tumor immunity such as apoptosis. In our study, DHL-TauZnNa showed an antiproliferative effect associated with autophagy in HT-29 cells, which exhibit resistance to apoptosis and chemoresistance (20), suggesting that DHL-TauZnNa may be a new therapeutic strategy against cancer cells with resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However the distinction between apoptosis and necrosis as immunogenic or nonimmunogenic forms of cell death respectively, may be too simplistic. Recent studies have shown that apoptotic death of tumor cells by certain agents (such as anthracyclines, proteasome inhibitors, or viral infection) can be immunogenic [16][17][18][19], while necrotic cell death may impair tumor immunity in vivo [20]. Moreover destroying the anthracycline induced apoptotic bodies by freeze thaw abolished their immunogenicity [18].…”
Section: Exposure Of Hsps During Cell Deathmentioning
confidence: 99%